Gastropods from the Burdwood Bank (southwestern Atlantic): an overview of species diversity - Luca, Javier Di; Zelaya, Diego G. (Zootaxa, 2019)
This contribution provides novel information on the diversity of gastropods from the Burdwood Bank, based on the material collected in this area, as part of the 2013 Summer Antarctic Expedition (“CAV 2013”), conducted by the oceanographic vessel PUERTO DESEADO. As part of this study, a total of 50 species are recognized, from which 19 are reported for the first time from Burdwood Bank, and at least nine other are probably new to science. Each species is here described and illustrated. The results arising from this study are combined with the previously published records in an attempt to critically compile the information for this area, with view to determine the local diversity of the group. As a result of this study, the diversity of gastropods almost double with respected to the previously published information, reaching a total of 79 species of shelled gastropods.